P240 Evaluating patient preferences of maintenance therapy for the treatment of chronic obstructive pulmonary disease in the UK: a discrete choice experiment. (December 2018) - Schroeder, M; Lewis, H; Doll, H; Gunsoy, NB; Llewellyn, S; Jones, PW; Ismaila, AS
Abstract : Purpose: With new single-inhaler triple therapies available for treatment of COPD, understanding patient preferences can be used to inform physicians' prescribing decisions and improving patient care. A discrete choice experiment (DCE) was conducted in the UK, Germany and USA. This abstract presents results from the UK only. Methods: Following qualitative research in patients with COPD, attributes describing features of COPD maintenance treatments were identified: ease of inhaler use (with an increasing number of mistakes to reduced efficacy/worsening of symptoms), number of exacerbations in the next year, daily frequency of inhaler use, number of different inhalers used and side-effects. The online DCE survey comprised 18 choice sets with logical (dominant) choice and consistency checks, along with demographic and disease history questions. Cognitive debriefing interviews and a pilot study confirmed the feasibility of the survey. The final DCE survey was completed by 150 patients in the UK. Responses to the DCE were analysed using mixed-effect logit models. Results: Of the 150 UK respondents, 146 (97.3%) answered the logical choice check correctly and were included in the final models; 119 (79.3%) selected the same choice within the consistency check. The odds ratios (ORs) for the majority of attributes were >1.0 and statistically significant, showing that for each unit benefit in the attribute (e.g., lower daily medication frequency, lower frequency of side effects), there is an increased likelihood of patients preferring the treatment (see table 1). The strongest drivers of treatment choice were relief of exacerbations (OR=2.22 for each unit reduction) and reduction of side effects (OR=4.59 for some and 11.65 for no side effects versus a lot of side effects). Conclusions: This study suggests that, in principle, patients in the UK with COPD place most importance on the reduction of symptoms and avoidance of side effects when choosing a treatment. However, inhaler number, ease and frequency of use were also important drivers of choice. Patient inhaler preference is important to consider when selecting COPD treatment as preference for an inhaler may improve treatment compliance. Funding: GSK study 2 06 455 (HO-16–16285); ICON received funding from GSK to conduct the study only.